2019
DOI: 10.1016/j.aquatox.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen sensitive liver transgenic zebrafish (Danio rerio) line (Tg(vtg1:mCherry)) suitable for the direct detection of estrogenicity in environmental samples

Abstract: Link to publication on Research at Birmingham portal General rights Unless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law. • Users may freely distribute the URL that is used to identify this publication. • Users may download and/or print one copy of the publication from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…50% of its LC 50 value (261 μg/L). In contrast, exposure levels for the four steroid hormones (E1, E2, E3 and EE2), as positive controls for the estrogenic effect, were all chosen to be 10 μg/L according to their 96-hpf EC 50 values of 2.9-8.9 μg/L (Segner et al, 2003;Van den Belt et al, 2004;Bakos et al, 2019). The control group was treated with 0.0025% acetone (Zhang et al, 2018); no obvious phenotypic malformations were observed for larval and adult zebrafish at this acetone concentration.…”
Section: Zebrafish Maintenance and Selection Criteria For Edc-exposurmentioning
confidence: 99%
“…50% of its LC 50 value (261 μg/L). In contrast, exposure levels for the four steroid hormones (E1, E2, E3 and EE2), as positive controls for the estrogenic effect, were all chosen to be 10 μg/L according to their 96-hpf EC 50 values of 2.9-8.9 μg/L (Segner et al, 2003;Van den Belt et al, 2004;Bakos et al, 2019). The control group was treated with 0.0025% acetone (Zhang et al, 2018); no obvious phenotypic malformations were observed for larval and adult zebrafish at this acetone concentration.…”
Section: Zebrafish Maintenance and Selection Criteria For Edc-exposurmentioning
confidence: 99%
“…Due to the strong relation of VTG protein for detecting estrogenicity effects at low levels in some strains, Bakos et al (2019) developed a transgenic zebrafish line (Tg(vtg1:mCherry)) natural vitellogenin-1 promoter sequence. Embryos 5 dpf of this zebrafish line were tested through a protocol based on the VTG and an estrogenic effect was detectable after seven generations and ZEA 100 ng/L, revealing the suitability of this model for detecting such effect and also the strong estrogenic capacity of ZEA (Schwartz et al, 2010;Bakos et al, 2013 and.…”
Section: Zearalenone and Its Metabolitesmentioning
confidence: 99%
“…Previously, Chen et al (2010) generated a transgenic line of ere ‐ zvtg1 : green fluorescent protein (GFP) zebrafish, which was reported to be responsive to 0.1 μg/L E2 and 1000 μg/L BPA administered for 13 days, as evidenced by green fluorescence accumulation. In another study, a transgenic line ( vtg1 :mCherry Tg fish) was reported to detect E2 at 0.1 μg/L after 2 days and 0.005 μg/L after 7 days and to measure the estrogenicity in wastewater samples, as reflected by the red fluorescence in the liver (Bakos et al, 2019).…”
Section: Resultsmentioning
confidence: 99%